Investigation on the self-assembled behaviors of C18 unsaturated fatty acids in arginine aqueous solution. Issue 66 (25th August 2017) - Wang, Yuxian; Jiang, Ling; Shen, Qinke; Shen, Jian; Han, Yuwang; Zhang, Hongman
Abstract : Self-assembled behaviors of UFAs in arginine solution have provided a theoretical basis for the application of two functional molecules in drug delivery. Abstract : In the field of drug delivery, there is growing concern over the self-assembly of fatty acids, since their structures and properties are similar to liposomes, which are characteristically nontoxic for humans, possess good biocompatibility and biodegradation, and are without immunogenicity. Changes in pH, temperature, concentration, molecular structure of the amphiphilic molecule, head group type and hydrocarbon chain length have significant effects on the self-assembled structures; however, the degree of unsaturation can also influence the self-assembled structures of fatty acids. The aggregation behaviors of the mixtures of arginine and three kinds of unsaturated fatty acids (UFAs, oleic acid, linoleic acid and linolenic acid) in aqueous solutions have been investigated. Phase transition from transparent micelles (L1 phase) to birefringent bilayer structures (Lα phase) occurred with increasing amounts of UFAs. However, the Lα phase was different for macro and micro structures. Oleic acid with only one double bond was regarded as less flexible and curved, but with higher stacking, leading to a gradual phase transition process from the vesicle phase to the stacked lamellar phase in the Lα phase region, which could be proved by cryogenic transmission electron microscopy (cryo-TEM) and polarizing microscopy observations combined with 2 H-nuclear magnetic resonance ( 2 H NMR) and rheological properties. The turbid vesicle phase with weak viscoelastic properties were only observed in linoleic acid and linolenic acid systems because UFAs with more than one double bond are easier to bend, indicating that highly curved vesicles are likely to form. Through the analysis of the proposed mechanism and FT-IR spectra, the synergistic effects of non-covalent interactions, including hydrogen bonding, electrostatic interaction, and hydrophobicity, were considered to be responsible for the aggregation behaviors. Finally, vesicles displayed their potential in encapsulating water-soluble model drugs such as calcein. The results show that drug-loaded vesicles could play a role in the potential applications in drug sustained delivery systems.